2019
DOI: 10.3803/enm.2019.34.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Type 2 Diabetes Mellitus in Primary Care Clinics in Korea

Abstract: BackgroundThis study investigated the overall status of diabetes control and screening for diabetic microvascular complications in patients with type 2 diabetes mellitus attending primary care clinics in Korea.MethodsIn this cross-sectional observational study, 191 primary care clinics were randomly selected across Korea from 2015 to 2016. In total, 3,227 subjects were enrolled in the study.ResultsThe patients followed at the primary care clinics were relatively young, with a mean age of 61.4±11.7 years, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…They found that the patients treated at primary care clinics had lower rates of achieving all three metabolic targets, with a rate of 5.9% compared to 21.5% for those who received care at the three tertiary hospitals. The screening rates for nephropathy, retinopathy, and neuropathy within the past 12 months at primary care clinics were 28.4%, 23.3%, and 13.3%, respectively [14]. These findings are consistent with those of other studies.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…They found that the patients treated at primary care clinics had lower rates of achieving all three metabolic targets, with a rate of 5.9% compared to 21.5% for those who received care at the three tertiary hospitals. The screening rates for nephropathy, retinopathy, and neuropathy within the past 12 months at primary care clinics were 28.4%, 23.3%, and 13.3%, respectively [14]. These findings are consistent with those of other studies.…”
supporting
confidence: 88%
“…However, few studies have investigated the comprehensive performance of HbA1c testing, lipid profiling, and screening for microvascular complications that include neuropathy in addition to nephropathy and retinopathy. In this issue, Seo et al [14] investigated the overall status of diabetes control and screening for diabetic microvascular complications in patients with T2DM attending 191 primary care clinics and three tertiary hospitals in 2015 and 2016 in Korea. They found that the patients treated at primary care clinics had lower rates of achieving all three metabolic targets, with a rate of 5.9% compared to 21.5% for those who received care at the three tertiary hospitals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Korea, oral medications are preferred for diabetes treatment, and insulin prescription rate is lower than that in other countries. Insulin is often used as the last treatment option, although its use has greatly increased by 4% to 19% in recent years [ 21 , 22 ]. The patient group treated with insulin within 2 to 4 years of diabetes diagnosis may be deemed susceptible to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed that the overall status of type 2 diabetes management, including HbA1c levels, blood pressure, and serum lipid levels, was suboptimal in primary care clinics in Korea. 8 According to this report, the screening rates for diabetic nephropathy and retinopathy within the past one year in 2,915 patients with type 2 diabetes were 28.4%, and 23.3%, respectively, at primary care clinics when compared with 87.8%, and 49.7%, respectively, at tertiary hospitals in Korea. 8 …”
Section: Discussionmentioning
confidence: 99%